ปัจจัยที่ส่งผลต่อผลสัมฤทธิ์การปฏิบัติราชการของโครงการชลประทานสกลนคร - Sansuwansri, Atigan; Romyen, Lamai; Swasthaisong, Sanyasorn (Journal of Graduate School Sakon Nakhon Rajabhat University, 2021)
The purposes of this research were: 1) to investigate the level of performance achievement of Sakon Nakhon Irrigation Projects, 2) to examine the level of factors in terms of work motivation and performance competency of Sakon Nakhon Irrigation Projects, and 3) to study the influences of factors-work motivation and performance competency affecting the performance achievement of Sakon Nakhon Irrigation Projects. The samples consisted of 268 personnel of Sakon Nakhon Irrigation Projects. The instrument employed for data collection including a set of questionnaires. Statistics for data analysis comprised frequency, percentage, mean, standard deviation, and multiple linear regression analysis. The findings revealed that: 1. The performance achievement of Sakon Nakhon Irrigation Projects as a whole were at the highest level ( = 4.51) 2. The work motivation of personnel as a whole was at a high level ( = 4.50) and performance competency of personnel as a whole was at a high level ( = 4.61). 3. Work motivation of personnel in term of the success of the performance (MOT2 ), accountability/ responsibility (MOT4), occupation progress (MOT3), occupation growth (MOT5) and workplace acknowledgement and recognition (MOT6) had significant influences on the performance results of Sakon Nakhon Irrigation Projects at the .05 level of significance with 0.175 coefficient and could correctly predict the performance results of Sakon Nakhon Irrigation Projects with 17.50 percent. 4. Performance competency of personnel of Sakon Nakhon Irrigation Projects in terms of functional/position competency (PER3), core competency (PER1), management competency (PER2) had significant influences on the performance achievement of Sakon Nakhon Irrigation Projects at the .05 level of significance with 0.108 coefficient and could predict the performance achievement of Sakon Nakhon Irrigation Projects with 10.80 percent.